Court advisers in Malaysia : a ‘Neglected’ component of the court for children? - Nur Ezaitie Nabihah Md Eusofe; Jal Zabdi Mohd Yusoff; Sridevi Thambapillay (Penerbit Universiti Kebangsaan Malaysia, 2022)
The court advisers are not a new component in the criminal justice system, especially in cases involving children. In most jurisdictions in the world, the court advisers (as known in Malaysia) or social workers/panel of advisers in other countries, are a component that was introduced to assist the judicial officer in determining a proper and suitable order for the child offenders. In Malaysia, children who have committed offences will be brought before the Court For Children (formerly known as the Juvenile Court). The Magistrate that presides the court will be assisted by two appointed court advisers. Although they comprise laymen without any legal qualification, their roles are recognised as equally important because they are the ones who are going to advise the Magistrate based on their knowledge and experience in dealing with children. In other words, the court advisers are a component that must exist in a trial so that a properly instituted quorum is constituted. The court advisers are introduced in the Juvenile Justice System for a reason. The court shall make sure that the court advisers are called and present throughout the trial. The court in the case of Public Prosecutor v Ayasamy [1955] 1 MLJ 64 highlighted this point more than 60 years ago. The logic is very simple, how can court advisers offer proper advice without attending the trial? Thus, in this article, the writers will explore the importance of making sure that the court advisers are present in the Court For Children trials. At the same time, the writers will also explore if there has been any development in the role and functions of the court advisers in Malaysia post the decision in the case of Public Prosecutor v Ayasamy. The reason being, more than six decades after the said case, the same issue was raised in the High Court’s decision in the case of Pendakwa Raya v Mohd Zairul Iman Zainon [2018] MLJU 578.